Application of Earth Tube Heat Exchanger and Solar Chimney for Natural Cooling System in Basrah City - Hammadi, Salman H.; Mohammed, Alaa Hlaichi (Basrah Journal for Engineering Sciences, 2014)
Solar chimney (SC) together with earth to air heat exchanger (EAHE) is being employed as a low-energy consuming technique to remove undesirable interior heat from a building in the hot seasons. A numerical program "FLUENT 6.3 code" of an earth to air heat exchanger (EAHE) is studied for predicting the outlet air temperature and cooling potential of these devices in Basrah climate. Theoretical analyses have been conducted in order to investigate the ventilation in a solar chimney. The investigation into the viability of Low Energy Earth Pipe Cooling Technology in providing thermal comfort in Basrah. The demand for air-conditioning in buildings in Basrah affects the country escalating energy consumption. Therefore, this investigation was intended to seek for an alternative passive cooling to air-conditioning. The passive technology, where the ground was used as a heat sink to produce cooler air, has not been investigated systematically in hot and humid countries. A sub-soil temperature model adapted for the specific conditions in Basrah is presented and its output compared with CFD modeling. The results have shown that the potential of Earth Pipe is providing lower output temperature of air inlet to the room. We found that the resulting temperature at the buried pipe outlet decreases with increasing pipe length, decreasing pipe diameter, decreasing mass flow rate of flowing air in the pipe and increasing depths up to 4m.